The Effect of The Existence of Internal Audit Function and Internal Audit Disclosure - Putri Retno Asri; Erfan Muhammad (Master of Accounting Universitas Trunojoyo Madura, 2021)
This study aims to examine and analyze the effect of the existence of an internal audit function (IAF) and internal audit disclosure (DIA) on external audit fees in non-financial companies listed on the Indonesia Stock Exchange in 2015-2019. The approach used in this study is a quantitative study consisting of 327 samples with purposive sampling technique. Data analysis in this study using multiple linear regression. The results showed that the existence of the internal audit function (IAF) had a negative and insignificant effect on the audit fee service, while the disclosure of the Internal Audit (DIA) had a significant positive effect on the fee service audit. Control variables, namely company size, return on assets, public accounting firms and subsidiaries are used to avoid it bias element.